Предмет: Математика, автор: lianamuhamedova04

решить удобным способом:
1) (-7)+(-8)+(+7)+(+7)=
2) (-1)+(+2)+(+1)+(-2)=
3) (-8)+(-6)+(-4)+(+28)=
4) (+19)-(-20)-(-39)+(-5)=​

Ответы

Автор ответа: ajtbubekbaeva
3

Ответ:

........................

Приложения:
Автор ответа: NataMon
2

Ответ:

1.   -1

2.  0

3.  10

4.  73

Пошаговое объяснение:

1) (-7)+(-8)+(+7)+(+7) =  (-7 + 7) + (-8 + 7) = 0 - 1 = -1

2) (-1)+(+2)+(+1)+(-2) =  (-1 + 1) + (2 - 2) = 0 + 0 = 0

3) (-8)+(-6)+(-4)+(+28) =  (-8 - 6 - 4) + 28 = -18 + 28 = 10

4) (+19)-(-20)-(-39)+(-5) =​ (19 - 5) - (-20 - 39) = 14 - (-59) = 14 + 59 = 73

Похожие вопросы
Предмет: Математика, автор: artemskibin04